PENGARUH PRESTASI KERJA DAN SENIORITAS TERHADAP PROMOSI JABATAN PADA PT. BANK BENGKULU CABANG UTAMA - Finthariasari, Meilaty; Sari, Desi Purnama (LPPM UNIVERSITAS BINA INSAN, 2020)
This study studies any factors that can improve the low performance of employees either partially or simultaneously. There are several factors that will be discussed in this study, discussed work Performance (X1), and seniority (X2). The object of this research is the company employees of PT Bank Bengkulu Cabang Utama, which gathered 60 people. The sampling method in this study is total sampling by taking an object or participating to take a sample. In this research the authors use the method of data collection by observation and questionnaires. There are several data analysis techniques used in this study, including using the instrument test, classic assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and also hypothesis testing. From the results of tests that have been carried out it can be concluded that the work performance reward and seniority variables have a partial or simultaneous effect on employee performance at PT Bank Bengkulu Cabang Utama.